PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENGANIAYAAN DI MUKA UMUM DALAM PERSPEKTIF KRIMINOLOGI - Ni Made Liana Dewi; A.A. Mas Adi Trinaya Dewi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
Not a few people are also involved in disagreements, fights that encourage them to commit mistreatment unintentionally so that it is felt that this criminal act of persecution can occur anywhere without knowing the place and can occur in public. Based on this background, the problem found is why someone commits a criminal act of mistreatment in public in terms of a criminology perspective at the Karangasem Resort Police, how is law enforcement against a criminal act of persecution in public in terms of a criminological perspective at the Karangasem Resort Police.The type of research in this study is empirical research with descriptive research. Data sources come from primary data sources and secondary data sources. The data collection technique used is Document Study, field research, interviews, and sample determination. Based on the data obtained and collected, it will be processed using qualitative analysis methods and then analyzed using inductive thinking methods. The conclusion obtained from this research is that there are several factors that cause the occurrence of criminal persecution. These factors are divided into 2 types, internal factors and external factors. The form of law enforcement against criminal acts of persecution in public from the perspective of criminology at the Karangasem Resort Police is divided into 3 forms, pre-emptive, preventive, and repressive.